2017
DOI: 10.1002/jhrm.21292
|View full text |Cite
|
Sign up to set email alerts
|

The effects of crew resource management on teamwork and safety climate at Veterans Health Administration facilities

Abstract: Communication failure is a significant source of adverse events in health care and a leading root cause of sentinel events reported to the Joint Commission. The Veterans Health Administration National Center for Patient Safety established Clinical Team Training (CTT) as a comprehensive program to enhance patient safety and to improve communication and teamwork among health care professionals. CTT is based on techniques used in aviation's Crew Resource Management (CRM) training. The aviation industry has reache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 59 publications
1
47
0
Order By: Relevance
“…Another study from the Veteran Administration hospitals report similar findings; they suggest that the improvement in participants' perception or belief that their specific facilities were doing more for patient safety than they had was linked to that the staff that participated in the team training interventions knew, observed, and /or understood that their leadership supported efforts to enhance patient safety in their clinical units [15].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Another study from the Veteran Administration hospitals report similar findings; they suggest that the improvement in participants' perception or belief that their specific facilities were doing more for patient safety than they had was linked to that the staff that participated in the team training interventions knew, observed, and /or understood that their leadership supported efforts to enhance patient safety in their clinical units [15].…”
Section: Discussionmentioning
confidence: 80%
“…The VA hospitals highlight briefing as a mechanism of communication before the start of shifts or procedures in clinical areas became part of the team's standardized communication [15]. Being present at daily meetings and in daily work is highlighted also by the managers in this study [15].…”
Section: Discussionmentioning
confidence: 86%
“…For example, an on-line module could be developed as required annual training for staff (Hughes et al, 2014). In studies of organizations after implementation of CRM, several researchers have found that without reinforcement and refresher training, staff experienced backsliding into previous behaviors (Kuy & Romero, 2017;Schwartz et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…While one additional study demonstrated a link between nursing units’ whose organization underwent safety training and decreased mortality rates (Thomas & Lomas, ), another study did not find an association between safety training and mortality after acute myocardial infarction (Shahian, Liu, Rossi, Mort & Normand, ). Schwartz and colleges implemented CRM immersive training at veteran's administration facilities and found that participating in the training improved communication, teamwork, and situational awareness for patient safety among workers (Schwartz et al, ). To the authors’ knowledge, no studies have investigated the link between comprehensive CRM training and the patient outcomes of FTR and inpatient mortality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation